Americans Experience Russia: Encountering the Enigma, 1917 to the Present - Chatterjee, Choi; Holmgren, Beth (Routledge Studies in Cultural History, 2013)
Americans Experience Russia analyzes how American scholars, journalists, and artists envisioned, experienced, and interpreted Russia/the Soviet Union over the last century. While many histories of diplomatic, economic, and intellectual connections between the United States and the Soviet Union can be found, none has yet examined how Americans' encounters with Russian/Soviet society shaped their representations of a Russian/Soviet 'other' and its relationship with an American 'west.' The essays in this volume critically engage with postcolonial theories which posit that a self-valorizing, unmediated west dictated the colonial encounter, repressing native voices that must be recovered. Unlike western imperialists and their colonial subjects, Americans and Russians long co-existed in a tense parity, regarding each other as other-than-European equals, sometime cultural role models, temporary allies, and political antagonists. In examining the fiction, film, journalism, treatises, and histories Americans produced out of their 'Russian experience,' the contributors to this volume closely analyze these texts, locate them in their sociopolitical context, and gauge how their producers' profession, politics, gender, class, and interaction with native Russian interpreters conditioned their authored responses to Russian/Soviet reality. The volume also explores the blurred boundaries between national identities and representations of self/other after the Soviet Union's fall.